Tweets et humour : le cas du Gorafi - Laurence Leveneur (Mise au Point)
In May 2012, during the French presidential campaign, a site of humorous information entitled Gorafi was created on the model of The Onion. At first a discussion thread on Twitter, Gorafi progressively became a blog, then a Web site. From 2014 until June 2015, it came in the form of a humorous clip in Le Grand Journal, a French television program broadcast on Canal+. Most of the articles on the Web site, largely leveraged on the socio-digital networks, comment on the current facts, real or imagined, in an offbeat way, resuming and diverting press and Web codes. Embodied on television by Pablo Mira, Gorafi presents an offbeat chronicle, which parodies the continuous news channels. As such, Gorafi offers a remarkable example of humour using a wide range of media, which I intend to explore in this paper. I will concentrate on short news items broadcast by the Gorafi team on Facebook and Twitter, and on the comments they generate, questioning whether these devices produce specific humorous codes.